Real-time marketing and PR : how to instantly engage your market, connect with customers, and create products that grow your business now - Scott, David Meerman (Hoboken, N.J. : Wiley, 2012)
"Launch effective real-time communications to win in today's always-on worldGone are the days when you could plan out your marketing and public relations programs well in advance and release them on your timetable. "Real time" means news breaks over minutes, not days. It means companies develop (or refine) products or services instantly, based on feedback from customers or events in the marketplace. And it's when businesses see an opportunity and are the first to act on it. In this eye-opening follow-up to The New Rules of Marketing and PR, a BusinessWeek bestseller, David Meerman Scott reveals the proven, practical steps to take your business into the real-time era.Find out how to act and react flexibly as events occur, position your brand in the always-on world of the Web, and avoid embarrassing mistakes and missteps. Real-Time Marketing and PR will also enable you to: Develop a business culture that encourages speed over sloth Read buying signals as people interact with your online information Crowdsource product development, naming, and even marketing materials such as online videos Engage reporters to shape stories as they are being written Command premium prices by delivering products at speed Deploy technology to listen in on millions of online discussions and instantly engage with customers and buyers Scale and media buying power are no longer a decisive advantage. What counts today is speed and agility. While your competitors scramble to adjust, you can seize the initiative, open new channels, and grow your brand. Master Real-Time Marketing and PR today and become the first to act, the first to respond, and the first to win!"--
Includes index.